ESTABLISHMENT OF EXPORT-ORIENTED ENTERPRISES (International journal of artificial intelligence, 2026)
This study comprehensively examines the theoretical foundations, organizational-economic mechanisms, and practical aspects of establishing export-oriented enterprises. The research analyzes the importance of export activities in the context of global economic integration, the necessity of increasing the competitiveness of national producers in international markets, and the factors influencing the development of export potential. The study describes in detail the stages of establishing export-oriented enterprises, including the formation of business ideas, market research, development of foreign trade strategies, attraction of investment, organization of production processes, and adaptation of products to international standards. Furthermore, the role of marketing, logistics, certification, customs procedures, and currency operations in organizing export activities is explored.The paper also analyzes state support mechanisms for exporters, including tax incentives, subsidies, export credits, and insurance systems. In addition, the role of small and medium-sized enterprises in export activities and the challenges they face in entering foreign markets are identified. As a result of the research, scientifically grounded proposals and recommendations are developed for the effective organization of export-oriented enterprises, increasing export volumes, improving the foreign trade balance, and ensuring the sustainable growth of the national economy.